Association between dietary inflammatory index and oral cancer risk: A systematic review and dose–response meta-analysis - Luo, Zhicheng; Zhu, Xidi; Hu, Yingyun; Yan, Shipeng; Chen, Lizhang (Frontiers in Oncology, 2022)
Background: Dietary inflammatory index (DII) has been suggested to be associated with oral cancer risk. However, a quantitative comprehensive assessment of the dose-response relationship has not been reported. We performed a meta-analysis to clarify the risk of oral cancer with DII. Methods: We searched PubMed, Embase, Cochrane Library, and Web of Science databases for relevant articles published up to March 1, 2022. Fixed or random effects models were utilized to estimate the pooled odds ratio (OR) of oral cancer with DII, as appropriate. Restricted cubic splines were used to model the dose-response relationship. Results: We included 5 case-control studies involving 1,278 cases and 5,137 controls in the meta-analysis. Risk of oral cancer was increased by 135% with the highest versus lowest DII level [OR: 2.35, 95% confidence interval (CI): 1.88-2.94], and 79% with higher versus lower DII level (OR: 1.79, 95% CI: 1.49-2.15). We found no evidence of a nonlinear dose-response association of DII with oral cancer (Pnon-linearity = 0.752), and the risk was increased by 17% (OR: 1.17, 95% CI: 1.05-1.30) with 1 unit increment in DII score. Conclusion: This meta-analysis suggested that higher DII score was associated with increased risk of oral cancer. Therefore, reducing pro-inflammatory components and promoting anti-inflammatory components of diet may be effective in the prevention of oral cancer.